ANALYSIS OF THE EFFECT OF TYPE OF WORK AND DURATION OF WORK AMONG PREGNANT WOMEN ON THE INCIDENCE OF LOW BIRTH WEIGHT - devi aprianti; Sunartono; Anas Rahmad Hidayat (Jurnal Penelitian, 2025)
Background: The Length of work is the period or the length of time that the workforce works in a place. The period starts from when a pregnant woman starts to work as an employee in a company until a certain period. Pregnant women who work too hard will spend a lot of energy and fatigue if not balanced with balanced food consumption and sufficient rest, then the nutritional needs of the fetus are not met properly, so that the weight in baby to be born has a small weight. Objective: Analyze the type of work and length of work of the mother during her pregnancy on the incidence of Low Birth Weight (LBW) at the UPTD Ma'u Health Center, Ma'u District, Nias Regency. Method: The research design used is a case-control study. In the case-control study, subject identification (cases) is carried out. Thus, there is a case group, namely mothers who gave birth to LBW babies, and a control group, namely mothers who gave birth to babies with normal weight at the Ma'u Health Center. The number of samples is 60 respondents, consisting of 30 respondents who gave birth to LBW babies and 30 respondents who gave birth to non-LBW babies. Univariate data analysis and bivariate analysis with chi-square test and linear regression test analysis. Results: Linear regression test f value count = 3.719 with a significance level of 0.030 <0.05, which means there is a real relationship with the presence of independent variables. When viewed from the significance value, there is a significant relationship between the type of work and the length of work on the incidence of LBW. Conclusion: a significant relationship between the type of work and length of work on the incidence of LBW.